2016
DOI: 10.3389/fnbot.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Rehabilitation of Ankle Plantar Flexors Spasticity: A 3-Month Study with Proprioceptive Neuromuscular Facilitation

Abstract: In this paper, we aim to investigate the effect of proprioceptive neuromuscular facilitation (PNF)-based rehabilitation for ankle plantar flexors spasticity by using a Robotic Ankle–foot Rehabilitation System (RARS). A modified robot-assisted system was proposed, and seven poststroke patients with hemiplegic spastic ankles participated in a 3-month robotic PNF training. Their impaired sides were used as the experimental group, while their unimpaired sides as the control group. A robotic intervention for the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In a future work, the foot-stretching technique used by each physical therapist and its effectiveness for the patient should be analyzed simultaneously to establish an effective stretching method. Moreover, several previous studies developed automatic machines for ankle stretching 15 , 16 , 17 , 18 ) . Although currently, no such machine has been commercialized, the analysis of foot-stretching techniques in this study will help in their development.…”
Section: Discussionmentioning
confidence: 99%
“…In a future work, the foot-stretching technique used by each physical therapist and its effectiveness for the patient should be analyzed simultaneously to establish an effective stretching method. Moreover, several previous studies developed automatic machines for ankle stretching 15 , 16 , 17 , 18 ) . Although currently, no such machine has been commercialized, the analysis of foot-stretching techniques in this study will help in their development.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there exist numerous robotic systems focused on sensory-motor rehabilitation of patients with motor problems from a neurological disorder; for instance, MIME [ 31 ], InMotion [ 32 ], NeReBot [ 33 ], among others [ 34 , 35 , 36 ]. Since the use of robotic devices specifically designed for neurorehabilitation has shown positive effects in motor function recovery [ 37 ], some studies have included a robotic device for treating the spasticity phenomenon [ 38 ]. However, the development of robot-aided systems aiming to evaluate the degree of upper limb spasticity is reduced.…”
Section: Spasticity Management: Assessment and Treatmentsmentioning
confidence: 99%
“…A possible explanation for this might be that the MAS is the most used scale among clinicians. The scale behaves better for upper limbs than for lower limbs, but even so, it is widely applied for measuring spasticity in the lower limb [ 38 ].…”
Section: Current Status Of Robot-aided Spasticity Assessment Systementioning
confidence: 99%
“…A previous study reported that an external output torque of approximately 13.5 Nm was required to assist dorsi exion movement from a drop foot posture [22]. Considering factors of individual differences and our application for subacute patients for full dorsi exion assistance during gait rehabilitation, the output torque of the system was set close to double, at 25 Nm.…”
Section: Requirements Of the High-dorsi Exion Assistive Robotic Systemmentioning
confidence: 99%